2020
DOI: 10.3390/antiox9080715
|View full text |Cite
|
Sign up to set email alerts
|

Natural-Based Antioxidant Extracts as Potential Mitigators of Fruit Browning

Abstract: Fruit enzymatic browning (EB) inhibition continues to be a challenge in the Food Industry. This physiological disorder results mainly from the oxidation of natural phenolic compounds by polyphenoloxidase (PPO) and peroxidase (POX) leading to the formation of brown pigments. EB can be controlled with the application of antioxidants, reducing/inhibiting the activity of these oxidative enzymes. In this study, strawberry tree (leaves and branches) and apple byproduct were the natural-based extracts (NES) selected,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 42 publications
(61 citation statements)
references
References 72 publications
1
56
0
Order By: Relevance
“…Likewise, in the ORAC method, CET followed by MAE BE apple extracts showed the highest antioxidant activity in the ABTS method, which is positively correlated (R 2 = 0.9644) with the higher TPC reported above. Furthermore, this behaviour has also been reported by Gómez-García et al [50] and Dias et al [51], who demonstrated a good correlation between total phenolic compounds and the antioxidant activity of melon peels and strawberry tree extracts, respectively, indicating that phenolic compounds are major contributors to antioxidant activity.…”
Section: Antioxidant Activitysupporting
confidence: 83%
“…Likewise, in the ORAC method, CET followed by MAE BE apple extracts showed the highest antioxidant activity in the ABTS method, which is positively correlated (R 2 = 0.9644) with the higher TPC reported above. Furthermore, this behaviour has also been reported by Gómez-García et al [50] and Dias et al [51], who demonstrated a good correlation between total phenolic compounds and the antioxidant activity of melon peels and strawberry tree extracts, respectively, indicating that phenolic compounds are major contributors to antioxidant activity.…”
Section: Antioxidant Activitysupporting
confidence: 83%
“…Sharma and Rao [17] reported that a xanthan gum-based edible coating incorporated with cinnamic acid led to a significant reduction of the oxidative browning process, which ultimately preserved the organoleptic characteristics of fresh-cut pears. Recently, Dias et al [18] selected, amongst fifteen natural-based extracts with antioxidant properties, strawberry tree (leaves and branches), as well as apple pomace methanolic extracts, as the most promising mitigators of fruit browning in fresh-cut pears. Total phenolic content of strawberry tree extracts (leaves and branches) were 207.9 mg and 104.1 mg GAE/g extract, respectively, and 6.8 mg GAE/g extract for apple pomace.…”
Section: Introductionmentioning
confidence: 99%
“…As reported in the literature, the applied solutions are a rich source of phenolic compounds [ 62 ]; thus, it was assumed that they may increase the pro-health properties of stored mung bean sprouts. It has been suggested that functional solutions are responsible for sprout fortification with phenolics; however, they rather act as elicitors, inducing de novo synthesis of phenolics.…”
Section: Resultsmentioning
confidence: 99%